EVALUASI DUKUNGAN SOSIAL EKONOMI UNTUK REHABILITASI LAHAN DAN KONSERVASI TANAH DI HULU DAS RANOYAPO KABUPATEN MINAHASA SELATAN PROPINSI SULAWESI UTARA - Robby D.J. Rempas; Hengki Walangitan; Wenny Tilaar (Universitas Sam Ratulangi, 2015)
ABSTRACT This study aims to (1) Description the level of socio-economic support for land rehabilitation and soil conservation around the upstream watershed Ranoyapo, (2) analyze the socio-economic factors and affect the support of farmers on land rehabilitation and soil conservation in the watershed upstream Ranoyapo Minahasa south. This research was conducted in the village of the District Mopolo Ranoyapo, Karowa village and sub-district Toraut New Tompaso and villages Mokobang Modoinding District of South Minahasa District. The variables were observed in this study is the level of support and socio- economic factors that have a relationship and affect support for land rehabilitation and soil conservation. The techniques of data collection will be done is prasurvey, the initial data collection in order to draft the research proposal. For variable rate of economic and social support relationship socioeconomic factors that affect the support classes were analyzed by assigning weights of 1 to 5 for each answer choice that is in the questionnaire. Total weight of all the answers to the questions will give a classification of the level of support each respondent farmers based on criteria of value support. Furthermore, the relationship socioeconomic factors that affect the support analyzed by non parameterik statistical approach that analyzes Pearson Product Moment assisted with SPSS applications. 3 The results showed the level of socio-economic support in land rehabilitation and soil conservation in the watershed upstream Ranoyapo strong and very powerful. For relationship socioeconomic factors that affect the level of support proved that the age factor of respondents have a relationship or positively correlated with support for land rehabilitation and soil conservation.. Education factor has no significant relationship to the socio-economic support in land rehabilitation and soil conservation. Results of this study resulted in several conclusions, namely: (1) The level of social support for the local economy in land rehabilitation and soil conservation in the watershed upstream Ranoyapo strong and very strong so the chances of success will be achieved. (2). Factor respondent's age has any relationship or positively correlated with support for land rehabilitation and soil conservation in the watershed upstream Ranoyapo whereas education and the status of the land factor not related or correlated with support for land rehabilitation and soil conservation.